Education reform: The New Zealand experience - Gary Hawke (New Zealand Institute of Economic Research (NZIER), 2002)
[Introduction] The New Zealand education system has experienced a great deal of change in the last 15 years or so. There is little desire for any wholesale reversal, and few would argue that the changes experienced have not included improvement. The description, `reform', is therefore seldom contested. However, much fine-tuning is still occurring and debates about particular refinements readily spill over into reconsideration of some of the major changes that have been implemented.
Keywords: 330; Bildungsreform; Neuseeland